70 Years of Levothyroxine - Kahaly, George J. (Springer Nature, 2021)
This open access book presents the history, pharmacokinetics and pharmacodynamics of levothyroxine, discussing its role in the thyroid pathophysiology of patients of various ages and during pregnancy. It also describes the influence of levothyroxine on heart, bone and in cancer. When it was first synthesized in 1949, levothyroxine represented a significant advance in the treatment of hypothyroidism, providing a safe and effective treatment option for millions of hypothyroid patients around the globe. This synthetic form of thyroxine is now one of the most prescribed drugs in the world. Levothyroxine was first introduced by Merck KGaA,Darmstadt, Germany, in 1972, and since then the company has remained actively engaged in research on this mainstay of hypothyroidism treatment. This book is intended for healthcare professionals.